A Polymer Coating Transfer Enrichment Method for Direct Mass Spectrometry Analysis of Lipids in Biofluid Samples. Issue 18 (27th March 2019) - Zhang, Wenpeng; Chiang, Spencer; Li, Zishuai; Chen, Qinhua; Xia, Yu; Ouyang, Zheng
Abstract: A porous polymer coating transfer enrichment method is developed for the direct mass spectrometry (MS) analysis of lipids. The enrichment is fast (ca. 1 min) and enables the profiling and quantitation of lipids in small‐volume biofluid samples. Coupled with a photochemical Paternò–Büchi reaction, this method enables the fast determination of lipid structure at the C=C location level and point‐of‐care lipid biomarker analysis. Abstract : A porous polymer coating transfer enrichment method was developed for the fast and direct mass spectrometry analysis of lipids in raw biofluid samples, enabling fast and reliable lipid profiling, detailed structure identification, and quantitation.